Is there an anti-inflammatory effect of aerobic exercises on axial spondyloarthropathy patients? A prospective, randomized-controlled trial - Yeşim Özge Gündüz Gül,; Ajda Bal,; Ümmü Gül Erdem, (Archives of Rheumatology, 2025)
Objectives: This study aims to examine whether aerobic exercises, in addition to home-based exercise (HBE) program, had anti-inflammatory effects, evaluated by disease activity, acute phase reactants, and cytokine levels in axial spondyloarthropathy (axSpA). Patients and methods: This two parallel-group, unblinded, 12-week, prospective, randomized-controlled trial (RCT) included a total of 54 participants who were followed for axSpa and the patients were equally allocated to the aerobic exercise group or HBE group. The aerobic exercise group included 27 patients (8 males, 19 females, mean age: 43.9±9.0 years; range, 27 to 58 years) and the HBE group included 27 patients (8 males, 19 females, mean age: 42.4±10.5 years; range, 23 to 63 years). The patients were evaluated using the Ankylosing Spondylitis Disease Activity Score (ASDAS), Visual Analog Scale (VAS), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI), chest expansion measurement, 6-Min Walk Test, and Ankylosing Spondylitis Quality of Life (ASQoL), Erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), tumor necrosis factoralpha (TNF-α) and interleukin-17 (IL-17) levels at the beginning of the study and after treatment completion. The HBE group was provided conventional exercise program. The second group ran on the treadmill in addition to their HBE program. Exercise sessions were performed three times a week for a period of 12 weeks. Results: After treatment, only the aerobic exercise group showed a significant improvement in disease activity (p<0.001). Both HBE and aerobic exercise groups showed a significant improvement in pain levels, functional statement, spinal mobility, chest expansion, functional exercise capacity, and life quality (p<0.001, p<0.001; p<0.001, p<0.001; p=0.03, p<0.001; p=0.008, p<0.001; p=0.004, p<0.001; p<0.001, and p<0.001, respectively). Only the HBE group showed a significant decrease in TNF-α levels and ESR (p=0.015, p=0.014). After treatment, the aerobic exercise group showed more improvement in disease activity, pain levels, functional exercise capacity, and quality of life compared to the HBE group (p<0.001, p=0.005, p<0.001, p=0.038). The change in post-treatment ESR, CRP, TNF-α, and IL-17 levels compared to pre-treatment did not show a statistically significant difference between the HBE and aerobic exercise groups (p>0.05). Conclusion: Adding aerobic exercise to a conventional exercise program may have an anti-inflammatory effect by reducing disease activity and help to manage disease.